A non-burned phosphogypsum dihydrate board and a preparation method thereof

CN122897652APending Publication Date: 2026-10-13CHINA BUILDING MATERIALS ACADEMY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610870670.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-16
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]为此,本发明提供一种二水磷石膏免烧板材及其制备方法,以解决现有技术中二水磷石膏免烧板材致密度不足(耐水性差、易吸水软化开裂)和强度不足的技术问题

Benefits of technology

本发明提供一种二水磷石膏免烧板材的制备方法,其中,所述制备方法包括如下步骤:S1,将二水磷石膏、晶型调控剂、塑性调节剂、矿物掺和料混合,得到混合粉体;S2,将溶剂、激发剂、离子调控剂、石膏晶须和有机相变材料-硅烷偶联剂胶囊混合,得到混合溶液;S3,将混合粉体和混合溶液混合,压制,得到二水磷石膏免烧板材;其中,所述压制包括至少两个阶梯式升温阶段,第n+1升温阶段的温度高于第n升温阶段的温度,n为大于等于1的正整数;(1)本发明分步骤进行,能够精准调控二水磷石膏的热力学溶解平衡,加速石膏晶体颗粒在(010)和(110)晶面方向的溶解蠕变和溶质的再结晶,加快其致密化堆积速率;(2)引入矿物掺和料能够实现长效致密化;(3)嵌入有机相变材料-硅烷偶联剂胶囊,通过耦合升温加压-降温泄压的动态工艺设计,控制有机相变材料-硅烷偶联剂胶囊缓释,强化界面相容性与疏水基团定向排布,加快石膏的溶解-沉淀速度,实现二水磷石膏免烧板材强度和耐水性能的长效提升;(4)本发明以二水磷石膏为核心原料,相较于传统煅烧法,无需经过脱水环节,工艺能耗显著降低;相较于传统压制后蒸压养护的免烧建材技术,省去高压蒸养工序,简化生产流程的同时进一步减少能耗与设备投入;(5)本发明二水磷石膏经脱硅浮选处理,能够有效脱除原料中惰性二氧化硅杂质,提升二水硫酸钙有效含量与纯度,优化颗粒形貌与粒径分布,减少界面缺陷与应力集中点,显著提升板材成型致密度、力学强度与耐水性能稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The application belongs to the technical field of building materials, and particularly relates to a dihydrate phosphogypsum non-burning plate and a preparation method thereof. The preparation method comprises the following steps: S1, dihydrate phosphogypsum, optional crystal form regulator, optional plasticity regulator and mineral admixture are mixed to obtain mixed powder; the dihydrate phosphogypsum is subjected to desilication flotation treatment; S2, a solvent, an activator, an ion regulator, gypsum whiskers and an organic phase change material-silane coupling agent capsule are mixed to obtain a mixed solution; S3, the mixed powder and the mixed solution are mixed and pressed to obtain the dihydrate phosphogypsum non-burning plate; wherein the pressing comprises at least two stepped temperature rising stages, the temperature of the (n+1)th temperature rising stage is higher than that of the nth temperature rising stage, and n is a positive integer greater than or equal to 1; the strength and compactness of the dihydrate phosphogypsum non-burning plate are improved, and compared with the prior art, part of the process steps are omitted, and energy consumption and equipment investment are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building materials technology, specifically relating to a non-fired phosphogypsum dihydrate board and its preparation method. Background Technology

[0002] Phosphogypsum (PG) is a solid waste generated during the wet process of phosphoric acid production in the phosphoric acid chemical industry, with approximately 80 million tons discharged annually and a comprehensive utilization rate of less than 60%. Since its main component is calcium sulfate dihydrate, it can be used to prepare various building materials such as cement retarders, gypsum boards, and gypsum mortars. Among these, using phosphogypsum to prepare gypsum boards has advantages such as high dosage, large market demand, and high product profits, making it a highly promising resource utilization method. However, traditional gypsum board production relies on a high-temperature calcination and dehydration process to produce building gypsum, followed by rehydration. This process is energy-intensive and produces significant carbon emissions. Furthermore, impurities such as phosphates and fluorides in phosphogypsum are difficult to completely remove through flotation and calcination alone, resulting in poor product performance stability. Therefore, there is an urgent need to develop a low-energy, low-cost gypsum board preparation process.

[0003] The formation of mineral layers in nature often involves complex geological evolution: particles containing the target mineral and aqueous solutions, under the slow synergistic effect of underground temperature and pressure environments, gradually complete a diagenetic cycle of "particle dissolution and creep - ion migration - solute precipitation." Water acts as a liquid carrier, causing solid mineral particles to undergo dissolution and creep, releasing ions. These ions migrate into the pores of the rock mass under weak pressure, eventually recrystallizing and precipitating under stable temperature and humidity conditions. Through dense cementation between particles, natural minerals with uniform structure and excellent mechanical strength are formed. The key to this natural diagenetic process lies in its densification driving force originating from the mineral's own dissolution-migration-precipitation, rather than the traditional compaction of soil and rock or the hydration process of cementing materials. Achieving densification through this method requires two core prerequisites: first, controllable solubility in the liquid phase to ensure the feasibility of ion migration; and second, sensitivity to environmental conditions such as temperature, humidity, and pressure, enabling a response that initiates the dissolution-precipitation process. Since calcium sulfate dihydrate, the main component of phosphogypsum, forms abundant sedimentary rocks in nature, theoretically, non-fired phosphogypsum dihydrate boards can be prepared by simulating the geological diagenetic process. Based on this, the present invention proposes to prepare dihydrate non-fired phosphogypsum boards by artificially controlling the temperature and pressure environment and liquid phase medium to simulate the core conditions of geological diagenesis.

[0004] However, there are three major problems with using this process for non-fired phosphogypsum dihydrate boards: (1) Difficulty in performance control: The process involves multiple continuous reactions under pressure conditions, including surface wetting, particle rearrangement, dissolution creep, solute migration, and recrystallization, which affect each other. This results in poor performance stability and insufficient strength. (2) Cost limitations: The pressure used in the actual large-scale production of building boards is relatively low. However, the solubility of phosphogypsum dihydrate in room temperature aqueous solution is low, resulting in low dissolution creep efficiency of non-fired phosphogypsum dihydrate boards under low pressure conditions, making it difficult to meet the requirements for building boards. (3) Shortcomings in water resistance: Pyrophyllite dihydrate itself is hydrophilic. When the board is in a humid environment, ion dissolution is likely to occur, resulting in a low softening coefficient, a significant decrease in strength, and phenomena such as powdering and cracking. This makes it unsuitable for humid environments such as basements and bathrooms, limiting its application scenarios. Summary of the Invention

[0005] Therefore, the present invention provides a non-fired board made of dihydrate phosphogypsum and its preparation method to solve the technical problems of insufficient density (poor water resistance, easy to absorb water, soften and crack) and insufficient strength of the non-fired board made of dihydrate phosphogypsum in the prior art.

[0006] Therefore, the present invention provides the following technical solution: The first aspect of this invention protects a method for preparing a non-fired board made of dihydrate phosphogypsum, wherein the preparation method includes the following steps: S1, mix dihydrate phosphogypsum, optional crystal form regulator, optional plasticity regulator, and mineral admixture to obtain a mixed powder; The dihydrate phosphogypsum was subjected to desilication flotation treatment; S2, the solvent, activator, ion regulator, gypsum whiskers and organic phase change material-silane coupling agent capsules are mixed to obtain a mixed solution; S3, mix the mixed powder and mixed solution, press them to obtain dihydrate phosphogypsum non-fired board; The pressing process includes at least two stepped heating stages, where the temperature of the (n+1)th heating stage is higher than the temperature of the nth heating stage, and n is a positive integer greater than or equal to 1.

[0007] In this invention, a compaction step is performed before the pressing step; the specific conditions are conventional conditions in the art, and typically, without limitation, the compaction time is 1-3 minutes.

[0008] In this invention, the pressing process includes a depressurization and cooling step after at least two stepped heating stages.

[0009] In this invention, after the pressing step, a curing and drying step is performed. The specific conditions are conventional conditions in the art. Typically, without limitation, the curing temperature is 20-25°C, the humidity is 55-60%, and the time is 7 or 28 days; the drying temperature is 40-45°C, and the time is 16-24 hours.

[0010] In the early stage of curing, the gel is generated and diffuses into the micropores through the ion mass transfer effect of internal moisture, achieving deep filling of the micropores. In the later stage of curing, a composite transition layer that is tightly bonded to the gypsum matrix is ​​generated by the formation of a delayed reaction reinforcing phase, which dynamically repairs any micro-damage that may occur later, significantly improving the strength and structural durability of phosphogypsum under low pressure.

[0011] In one optional embodiment, the raw materials for the dihydrate phosphogypsum non-fired board include: 40-80 parts by weight of dihydrate phosphogypsum, 5-10 parts by weight of solvent, 0.1-0.5 parts by weight of gypsum whiskers, 0.1-0.5 parts by weight of crystal form regulator, 0.1-0.5 parts by weight of ion regulator, 0.1-0.5 parts by weight of plasticity regulator, 0.5-1.5 parts by weight of mineral admixture, 0.1-0.5 parts by weight of activator, and 0.1-1.0 parts by weight of organic phase change material-silane coupling agent capsules.

[0012] In one optional embodiment, the raw materials for the dihydrate phosphogypsum non-fired board include: 50-70 parts by weight of dihydrate phosphogypsum, 6-8 parts by weight of solvent, 0.1-0.3 parts by weight of gypsum whiskers, 0.1-0.3 parts by weight of crystal form regulator, 0.2-0.5 parts by weight of ion regulator, 0.3-0.5 parts by weight of plasticity regulator, 0.6-1.2 parts by weight of mineral admixture, 0.1-0.3 parts by weight of activator, and 0.5-1.0 parts by weight of organic phase change material-silane coupling agent capsules.

[0013] In one alternative implementation, the pressing includes two stepped heating stages.

[0014] In one optional embodiment, the pressing conditions include: starting from an initial state of 20-25°C and standard atmospheric pressure (1 atm), increasing the pressure to 5-20 MPa at a rate of 0.1-0.5 MPa / s and maintaining the pressure constant; heating to 35-50°C at a rate of 5-15°C / min and maintaining the pressure and temperature for 1-10 min; maintaining the pressure constant, continuing to increase the temperature to 60-80°C at a rate of 5-15°C / min and maintaining the pressure and temperature for 1-10 min; stopping heating and simultaneously unloading the pressure at a rate of 0.1-0.3 MPa / s; after depressurization, allowing the material to cool naturally to 20-25°C before removing it.

[0015] In one optional embodiment, the pressing conditions include: starting from an initial state of 20-25°C and standard atmospheric pressure, increasing the pressure to 10-15 MPa at a rate of 0.1-0.3 MPa / s and maintaining the pressure constant, heating to 35-40°C at a rate of 8-12°C / min and maintaining the pressure and temperature for 1-5 min; maintaining the pressure constant, continuing to increase the temperature to 60-65°C at a rate of 8-12°C / min and maintaining the pressure and temperature for 1-5 min.

[0016] In one alternative embodiment, the organic phase change material of the organic phase change material-silane coupling agent capsule serves as the shell material, and the silane coupling agent serves as the core material.

[0017] In one optional embodiment, the organic phase change material-silane coupling agent capsule has a particle size of 5-20 μm, a shell thickness of 1-3 μm, a phase change enthalpy of 80-100 J / g, and a shell breaking temperature of 60-65℃.

[0018] In one optional embodiment, the mass ratio of the silane coupling agent to the organic phase change material is (3-4):(6-7).

[0019] In one alternative embodiment, the organic phase change material comprises polycaprolactone and / or phase change paraffin.

[0020] In one optional embodiment, the silane coupling agent includes at least one of KH-550 silane coupling agent, KH-540 silane coupling agent, and KH-792 silane coupling agent.

[0021] In one optional embodiment, the preparation method of the organic phase change material-silane coupling agent capsule includes the following steps: (1) Mix the organic phase change material, silane coupling agent, and good solvent to obtain the oil phase; (2) Mix water and emulsifier to obtain an aqueous phase; (3) Add the oil phase to the water phase and mix to obtain an O / W type emulsion. Heat, separate, wash and dry to obtain organic phase change material-silane coupling agent capsules.

[0022] Step (1) of this invention includes the following steps: (1-1) Mix the organic phase change material with a good solvent to obtain a shell material solution; (1-2) The shell material solution and silane coupling agent are mixed to obtain the oil phase; The concentration of the organic phase change material in the shell material solution is 5-10 wt%; the good solvent includes at least one of dichloromethane, trichloromethane, and tetrahydrofuran.

[0023] In steps (1-2) of this invention, mixing is carried out by stirring, specifically under the conditions of stirring at 300-500 rpm for 15-20 minutes.

[0024] In step (2) of this invention, the mass ratio of water to emulsifier is (200-300):1; the emulsifier is a conventional emulsifier in the art, typically and non-limitingly including at least one of polyvinyl alcohol, polysorbate 80, and sodium dodecyl sulfate; the water is conventional water in the art, typically and non-limitingly using deionized water. Mixing is performed by stirring, typically and non-limitingly at 200-300 rpm for 5-10 minutes until the emulsifier is completely dissolved, obtaining an aqueous phase; during mixing, dilute hydrochloric acid or sodium hydroxide solution is also added to adjust the pH to 7-8.

[0025] In step (3) of the present invention, at 25°C, the oil phase is added dropwise to the aqueous phase at a rate of 1-3 mL / min and mixed by stirring at 800-1200 rpm for 20-30 min; the heating temperature is 45°C, the stirring speed is 300-500 rpm, and the time is 6-10 h.

[0026] Specifically, the preparation method of the polycaprolactone-silane coupling agent capsule includes the following steps: (1) dissolving polycaprolactone in dichloromethane to form a shell material solution with a mass concentration of 5%-10%; adding KH550 silane coupling agent to the shell material solution at a core-shell mass ratio of 3:7-4:6, and stirring at 300-500 rpm for 15-20 min until the mixture is uniform to obtain an oil phase; (2) mixing deionized water and emulsifier at a mass ratio of 200:1, adjusting the pH value to 7-8 with dilute hydrochloric acid or sodium hydroxide solution, and stirring at 200-300 rpm for 5-10 min until the emulsifier is completely dissolved. (3) The oil phase is added dropwise to the aqueous phase at a rate of 1-3 mL / min at 20-25℃, and stirred at 800-1200 rpm for 20-30 min to form an O / W type emulsion; the emulsion is placed in a constant temperature water bath at 35-45℃ and stirred at 300-500 rpm for 6-8 h to allow dichloromethane to evaporate. After the shell solidifies, the solid particles are separated by filtration; the solid particles are washed with deionized water 3-5 times and dried at 35-40℃ and vacuum degree -0.08 to -0.09 MPa for 12 h to obtain polycaprolactone-silane coupling agent capsules.

[0027] In an optional embodiment, the CaSO4 of the dihydrate phosphogypsum The 2H2O content is ≥85wt%, the SiO2 content is ≤5wt%, the median particle size is 50-150μm, the residue on a 0.15mm square hole sieve is ≤5wt%, and it is in the form of flakes.

[0028] In one optional embodiment, the desilication flotation includes the following steps: mixing the material after sieving dihydrate phosphogypsum through a 0.15mm square hole sieve with water, dispersant, inhibitor, cationic collector, and frother, performing a coarse-scavenging reverse flotation, filtering, and drying.

[0029] Optionally, the mass ratio of material to water is 1:(2-4).

[0030] Optionally, the mass ratio of the material to the dispersant is 10000:(1-5).

[0031] Optionally, the dispersant includes at least one of water glass, sodium hexametaphosphate, and sodium fluoride.

[0032] Optionally, the mass ratio of the material to the inhibitor is 10000:(1-5).

[0033] Optionally, the inhibitor includes at least one of starch and carboxymethyl cellulose.

[0034] Optionally, the mass ratio of the material to the cationic collector is 10000:(1-5).

[0035] Optionally, the cationic collector includes at least one of tetradecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, and octadecyltrimethylammonium chloride.

[0036] Optionally, the mass ratio of the material to the foaming agent is 10000:(1-5).

[0037] Optionally, the foaming agent includes at least one of methyl isobutyl methanol and pine oil.

[0038] Optionally, the conditions for reverse flotation include: a temperature of 20-25℃, a stirring speed of 1500-2000 r / min, a roughing flotation time of 3-8 min, and a scavenging flotation time of 3-8 min.

[0039] In this invention, filtration and drying are conventional conditions in the art, typically and non-limitingly, drying at 40-60°C for 30-90 minutes.

[0040] In one alternative embodiment, the crystal form regulator comprises anhydrous gypsum and / or citric acid.

[0041] In one optional embodiment, the anhydrous gypsum is type II anhydrous gypsum with a CaSO4 content ≥90wt% and a median particle size of 40-100μm.

[0042] In one alternative embodiment, the plasticity modifier includes at least one of talc, mica, and montmorillonite.

[0043] Optionally, the talc powder has a SiO2 content ≥60wt%, an MgO content ≥30wt%, and a median particle size of 3-10μm.

[0044] In one optional embodiment, the mineral admixture includes blast furnace slag powder and / or fly ash; Optionally, the blast furnace slag powder conforms to GB / T 18046-2017 standard and has a specific surface area of ​​350-450 m². 2 / kg, 7d activity index ≥75%, 28d activity index ≥95%; Optionally, the fly ash is Grade I fly ash, conforming to GB / T 1596-2017 standard, with a loss on ignition ≤5wt% and a specific surface area ≥300m² / kg.

[0045] In one alternative embodiment, the activator comprises sodium hydroxide and / or potassium hydroxide.

[0046] Optionally, the sodium hydroxide is industrial-grade flake caustic soda with a purity ≥96wt%, a moisture content ≤1wt%, and an insoluble content ≤0.05wt%.

[0047] In one optional embodiment, the ion regulator includes at least one of sodium chloride, sodium sulfate, potassium chloride, and aluminum sulfate; in this invention, the ion regulators are all industrial-grade chemical raw materials.

[0048] In one alternative embodiment, the gypsum whiskers comprise α-type calcium sulfate hemihydrate whiskers and / or β-type calcium sulfate hemihydrate whiskers.

[0049] Optionally, the gypsum whiskers have a length of 50-200 μm, a diameter of 1-5 μm, and an aspect ratio of (20-50):1.

[0050] In this invention, the solvent is a conventional solvent in the art, and typically, without limitation, the solvent includes water.

[0051] In one optional implementation, in step S1, the mixing speed is 400-600 rpm and the time is 10-15 min.

[0052] In one optional implementation, in step S2, the mixing speed is 300-500 rpm and the time is 3-5 min.

[0053] In one optional implementation, in step S3, the mixing speed is 120-180 rpm and the mixing time is 5-10 min.

[0054] The second aspect of this invention protects a non-fired board made of dihydrate phosphogypsum prepared by the aforementioned preparation method.

[0055] The technical solution of this invention has the following advantages: This invention provides a method for preparing a non-fired board of phosphogypsum dihydrate, wherein the preparation method includes the following steps: S1, mixing phosphogypsum dihydrate, crystal form regulator, plasticity regulator, and mineral admixture to obtain a mixed powder; S2, mixing solvent, activator, ion regulator, gypsum whiskers, and organic phase change material-silane coupling agent capsules to obtain a mixed solution; S3, mixing the mixed powder and the mixed solution, pressing to obtain a non-fired board of phosphogypsum dihydrate; wherein the pressing includes at least two stepped heating stages, the temperature of the (n+1)th heating stage is higher than the temperature of the nth heating stage, and n is a positive integer greater than or equal to 1; (1) This invention is carried out in steps, which can accurately control the thermodynamic dissolution balance of phosphogypsum dihydrate, accelerate the dissolution creep of gypsum crystal particles in the (010) and (110) crystal plane directions and the recrystallization of solute, and accelerate its densification and stacking rate; (2) The introduction of mineral admixture can achieve long-term densification; (3) (4) The present invention uses phosphogypsum dihydrate as the core raw material. Compared with the traditional calcination method, it does not need to go through the dehydration process, and the process energy consumption is significantly reduced. Compared with the traditional non-fired building material technology of pressing and steam curing, it eliminates the high pressure steam curing process, simplifies the production process, and further reduces energy consumption and equipment investment. (5) The phosphogypsum dihydrate of the present invention is treated by desilication flotation, which can effectively remove inert silica impurities in the raw material, improve the effective content and purity of calcium sulfate dihydrate, optimize the particle morphology and particle size distribution, reduce interface defects and stress concentration points, and significantly improve the molding density, mechanical strength and water resistance stability of the board. Detailed Implementation

[0056] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.

[0057] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention; the terms “comprising” and “having” and any variations thereof in the text of this invention are intended to cover non-exclusive inclusion.

[0058] In the description of the embodiments of the present invention, the technical terms "first", "second", etc. are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.

[0059] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of the invention. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0060] The "range" disclosed in this invention is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the specific range. This range can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. In this invention, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers from a to b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed herein; "0-5" is merely a shortened representation of these numerical combinations. Furthermore, when a parameter is described as an integer ≥ 2, it is equivalent to disclosing that the parameter can be, for example, an integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0061] In the description of the embodiments of the present invention, the term "and / or" is merely a description of the relationship between associated objects, indicating that there can be three relationships. For example, A and / or B can represent three situations: A exists alone, A and B exist simultaneously, and B exists alone.

[0062] In the description of the embodiments of the present invention, the term "at least one" refers to one or more (including two).

[0063] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.

[0064] Dihydrate phosphogypsum No. 1 is a raw material of dihydrate phosphogypsum after desilication flotation, CaSO4. The 2H2O content is 92wt%, the SiO2 content is 1.2wt%, the median particle size is 62μm, and the residue on a 0.15mm square-hole sieve is 2wt%, appearing as flakes. The specific desilication flotation process includes: pre-screening the dihydrate phosphogypsum residue through a 0.15mm square-hole sieve, discarding the coarse particles on the sieve, mixing the undersize material with water at a mass ratio of 1:3, and stirring for 2 minutes; adding water glass at a mass ratio of 10000:3, and stirring for 2 minutes; adding starch at a mass ratio of 10000:4. Stir for 2 minutes; add tetradecyltrimethylammonium chloride, with a mass ratio of material to tetradecyltrimethylammonium chloride of 10000:1, and stir for 2 minutes; add methyl isobutyl methanol, with a mass ratio of material to methyl isobutyl methanol of 10000:2, and stir for 2 minutes; use an XFD type single-cell flotation machine to carry out one roughing and one scavenging reverse flotation at 25℃ and a stirring speed of 1800 r / min, with a roughing flotation time of 5 minutes and a scavenging flotation time of 5 minutes; filter the product at the bottom of the flotation cell and dry it with hot air at 55℃ for 60 minutes; Dihydrate phosphogypsum No. 2 is a dihydrate phosphogypsum raw material that has not undergone desilication flotation, CaSO4 The 2H2O content is 85wt%, the SiO2 content is 4.8wt%, the median particle size is 62μm, the residue on a 0.15mm square hole sieve is 4wt%, and it is in the form of flakes; The calcium sulfate hemihydrate whiskers are α-type calcium sulfate hemihydrate whiskers with an average length of 100 μm, an average diameter of 3 μm, and an aspect ratio of 25:1. The anhydrous gypsum is type II anhydrous gypsum, with a CaSO4 content of 93 wt% and a median particle size of 68 μm; Sodium chloride: Industrial grade; Sodium sulfate: Industrial grade; The talc powder has a SiO2 content of 60.2 wt%, an MgO content of 30.1 wt%, and a median particle size of 5 μm. The mica powder contains 49 wt% SiO2 and 30 wt% Al2O3. The fly ash is Class I fly ash, conforming to GB / T 1596-2017 standard, with a loss on ignition of 3.8 wt% and a specific surface area of ​​320 m². 2 / kg; Blast furnace slag powder, conforming to GB / T 18046-2017 standard, with a specific surface area of ​​400 m². 2 / kg, the activity index was 75% at 7 days and 95% at 28 days; Sodium hydroxide: Industrial grade flaky caustic soda, purity ≥96wt%, moisture content ≤1wt%, insoluble matter content ≤0.05wt%; Potassium hydroxide: Industrial grade; The preparation method of polycaprolactone-silane coupling agent capsule No. 1 includes: dissolving polycaprolactone (weight-average molecular weight of 90,000) in dichloromethane to form a shell material solution with a mass concentration of 8 wt%; adding KH-550 silane coupling agent to the shell material solution at a core-shell mass ratio of 3:7; and stirring at 400 rpm for 18 min until homogeneous to obtain an oil phase; mixing deionized water and emulsifier (sodium dodecyl sulfate) at a mass ratio of 200:1; adjusting the pH to 7; and stirring at 250 rpm for 8 min until the emulsifier dissolves to obtain an aqueous phase; and then mixing the oil phase with 2... The polycaprolactone-silane coupling agent was added dropwise to the aqueous phase at a rate of mL / min at 25℃ and stirred at 1000 rpm for 25 min to form an O / W emulsion. The emulsion was placed in a 35℃ water bath and stirred at 500 rpm for 6 h to allow dichloromethane to evaporate. After the shell solidified, the solid particles were separated by vacuum filtration, washed three times with deionized water, and dried at 40℃ under a vacuum of -0.08 MPa for 12 h to obtain polycaprolactone-silane coupling agent capsule No. 1. The median particle size was 15 μm, the shell thickness was 2 μm, the phase transition enthalpy was 85.63 J / g, and the shell breaking temperature was 61℃. One part by weight in the examples and comparative examples corresponds to 1 kg.

[0065] Example 1 This embodiment provides a non-fired board made of dihydrate phosphogypsum and its preparation method. Raw material for non-fired boards made from dihydrate phosphogypsum: 60 parts by weight of dihydrate phosphogypsum No. 1, 6 parts by weight of water, 0.2 parts by weight of hemihydrate calcium sulfate whiskers, 0.2 parts by weight of anhydrous gypsum, 0.3 parts by weight of sodium chloride, 0.4 parts by weight of talc, 0.9 parts by weight of fly ash, 0.2 parts by weight of sodium hydroxide, and 0.7 parts by weight of polycaprolactone-silane coupling agent capsule No. 1. The preparation method includes the following steps: S1. Mix dihydrate phosphogypsum No. 1, anhydrous gypsum, talc powder, and fly ash according to their mass, add them to a mixer, and mix thoroughly at 500 rpm for 12 minutes to obtain a mixed powder. S2, mix water, sodium hydroxide, sodium chloride, calcium sulfate hemihydrate whiskers and polycaprolactone-silane coupling agent capsules, and stir at a low speed of 400 rpm for 4 minutes to obtain a mixed solution; S3. Mix the powder and solution using a cement mortar mixer for 8 minutes until the material is evenly dispersed and the powder surface is completely wetted to obtain a mixed wet material. Then pour the mixed wet material into a compaction mold and place it on a vibrating table to compact for 2 minutes until the surface is smooth. S4. Place the compaction mold containing the mixed wet material into the pressure equipment. Starting from an initial state of 25℃ and 1 atm, pressurize to 10MPa at a rate of 0.2MPa / s and maintain the pressure. Heat to 40℃ at a rate of 10℃ / min and maintain the pressure and temperature for 5 minutes. Keep the pressure constant and continue to raise the temperature to 65℃ at a rate of 10℃ / min and maintain the pressure and temperature for 5 minutes. Stop heating and simultaneously unload the pressure at a rate of 0.2MPa / s. After depressurization, allow the material to cool naturally to 25℃ before removing it. S5. Demold the molded blanks and divide them into A and B according to their weight. Place A in an environment with a temperature of 25℃ and a humidity of 55% for 7 days. After curing, dry it at 40℃ for 24 hours to obtain dihydrate phosphogypsum non-fired board (7d). Place B in an environment with a temperature of 25℃ and a humidity of 55% for 28 days. After curing, dry it at 40℃ for 24 hours to obtain dihydrate phosphogypsum non-fired board (28d).

[0066] Example 2 This embodiment provides a non-fired board made of dihydrate phosphogypsum and its preparation method. Raw material for non-fired boards made from dihydrate phosphogypsum: 60 parts by weight of dihydrate phosphogypsum No. 1, 6 parts by weight of water, 0.3 parts by weight of hemihydrate calcium sulfate whiskers, 0.3 parts by weight of anhydrous gypsum, 0.4 parts by weight of sodium chloride, 0.5 parts by weight of talc, 1.2 parts by weight of fly ash, 0.3 parts by weight of sodium hydroxide, and 1 part by weight of polycaprolactone-silane coupling agent capsule No. 1. The preparation method was the same as in Example 1, and phosphogypsum dihydrate unfired boards (7d) and phosphogypsum dihydrate unfired boards (28d) were obtained respectively.

[0067] Example 3 This embodiment provides a non-fired board made of dihydrate phosphogypsum and its preparation method. Raw material for non-fired boards made from dihydrate phosphogypsum: 60 parts by weight of phosphogypsum dihydrate No. 1, 6 parts by weight of water, 0.3 parts by weight of calcium sulfate hemihydrate whiskers, 0.2 parts by weight of citric acid, 0.3 parts by weight of sodium sulfate, 0.4 parts by weight of mica powder, 1.2 parts by weight of blast furnace slag powder, 0.3 parts by weight of potassium hydroxide, and 0.7 parts by weight of polycaprolactone-silane coupling agent capsule No. 1. The preparation method includes the following steps: S1. Mix phosphogypsum dihydrate No. 1, citric acid, mica powder, and blast furnace slag powder according to their mass, add them to a mixer, and mix thoroughly at 500 rpm for 12 minutes to obtain a mixed powder. S2, mix water, potassium hydroxide, sodium sulfate, calcium sulfate hemihydrate whiskers and polycaprolactone-silane coupling agent capsules at a low speed of 400 rpm for 4 min to obtain a mixed solution; S3. Mix the powder and solution using a cement mortar mixer for 8 minutes until the material is evenly dispersed and the powder surface is completely wetted to obtain a mixed wet material. Then pour the mixed wet material into a compaction mold and place it on a vibrating table to compact for 2 minutes until the surface is smooth. S4. Place the compaction mold containing the mixed wet material into the pressure equipment. Starting from an initial state of 25℃ and 1 atm, pressurize to 10MPa at a rate of 0.2MPa / s and maintain the pressure. Heat to 40℃ at a rate of 10℃ / min and maintain the pressure and temperature for 5 minutes. Keep the pressure constant and continue to raise the temperature to 65℃ at a rate of 10℃ / min and maintain the pressure and temperature for 5 minutes. Stop heating and simultaneously unload the pressure at a rate of 0.2MPa / s. After depressurization, allow the material to cool naturally to 25℃ before removing it. S5. Demold the molded blanks and divide them into A and B according to their weight. Place A in an environment with a temperature of 25℃ and a humidity of 55% for 7 days. After curing, dry it at 40℃ for 24 hours to obtain dihydrate phosphogypsum non-fired board (7d). Place B in an environment with a temperature of 25℃ and a humidity of 55% for 28 days. After curing, dry it at 40℃ for 24 hours to obtain dihydrate phosphogypsum non-fired board (28d).

[0068] Example 4 This embodiment provides a non-fired board made of dihydrate phosphogypsum and its preparation method. Raw material for non-fired boards made from dihydrate phosphogypsum: 60 parts by weight of dihydrate phosphogypsum No. 1, 6 parts by weight of water, 0.1 parts by weight of hemihydrate calcium sulfate whiskers, 0.1 parts by weight of anhydrous gypsum, 0.3 parts by weight of sodium chloride, 0.4 parts by weight of talc, 0.9 parts by weight of fly ash, 0.2 parts by weight of sodium hydroxide, and 0.5 parts by weight of polycaprolactone-silane coupling agent capsule No. 1. The preparation method was the same as in Example 1, and phosphogypsum dihydrate unfired boards (7d) and phosphogypsum dihydrate unfired boards (28d) were obtained respectively.

[0069] Example 5 This embodiment provides a non-fired board made of dihydrate phosphogypsum and its preparation method. Raw material for non-fired boards made from dihydrate phosphogypsum: 60 parts by weight of dihydrate phosphogypsum No. 1, 6 parts by weight of water, 0.1 parts by weight of hemihydrate calcium sulfate whiskers, 0.1 parts by weight of anhydrous gypsum, 0.2 parts by weight of sodium chloride, 0.3 parts by weight of talc, 0.6 parts by weight of fly ash, 0.1 parts by weight of sodium hydroxide, and 0.5 parts by weight of polycaprolactone-silane coupling agent capsule No. 1. The preparation method was the same as in Example 1, and phosphogypsum dihydrate unfired boards (7d) and phosphogypsum dihydrate unfired boards (28d) were obtained respectively.

[0070] Example 6 This embodiment provides a non-fired board made of dihydrate phosphogypsum and its preparation method. Raw materials for non-fired phosphogypsum dihydrate boards: 40 parts by weight of phosphogypsum dihydrate No. 1, 5 parts by weight of water, 0.4 parts by weight of calcium sulfate hemihydrate whiskers, 0.5 parts by weight of anhydrous gypsum, 0.1 parts by weight of sodium chloride, 0.2 parts by weight of talc, 1 part by weight of fly ash, 0.4 parts by weight of sodium hydroxide, and 0.3 parts by weight of polycaprolactone-silane coupling agent capsule No. 1. The preparation method was the same as in Example 1, and phosphogypsum dihydrate unfired boards (7d) and phosphogypsum dihydrate unfired boards (28d) were obtained respectively.

[0071] Example 7 This embodiment provides a non-fired board made of dihydrate phosphogypsum and its preparation method. Raw material for dihydrate phosphogypsum-free board: according to the method in Example 1; The preparation method includes the following steps: S1, according to the method of Example 1; S2, according to the method of Example 1; S3, according to the method of Example 1; S4. Place the compaction mold containing the mixed wet material into the pressure equipment. Starting from an initial state of 25℃ and 1 atm, pressurize to 10MPa at a rate of 0.5MPa / s and maintain the pressure. Heat to 48℃ at a rate of 5℃ / min and maintain the pressure and temperature for 8 minutes. Keep the pressure constant and continue to increase to 70℃ at a rate of 5℃ / min and maintain the pressure and temperature for 8 minutes. Stop heating and simultaneously unload the pressure at a rate of 0.2MPa / s. After depressurization, allow the material to cool naturally to 25℃ before removing it. S5, following the method of Example 1, phosphogypsum dihydrate unfired board (7d) and phosphogypsum dihydrate unfired board (28d) were obtained respectively.

[0072] Example 8 This embodiment provides a non-fired board made of dihydrate phosphogypsum and its preparation method. Raw material for non-fired boards made from dihydrate phosphogypsum: 60.2 parts by weight of phosphogypsum dihydrate No. 1, 6 parts by weight of water, 0.2 parts by weight of calcium sulfate hemihydrate whiskers, 0.3 parts by weight of sodium chloride, 0.4 parts by weight of talc, 0.9 parts by weight of fly ash, 0.2 parts by weight of sodium hydroxide, and 0.7 parts by weight of polycaprolactone-silane coupling agent capsule No. 1. The preparation method includes the following steps: S1. Mix phosphogypsum dihydrate No. 1, talc powder, and fly ash according to their mass, add them to a mixer, and mix thoroughly at 500 rpm for 12 minutes to obtain a mixed powder. S2, according to the method of Example 1; S3, according to the method of Example 1; S4, according to the method of Example 1; S5, following the method of Example 1, phosphogypsum dihydrate unfired board (7d) and phosphogypsum dihydrate unfired board (28d) were obtained respectively.

[0073] Example 9 This embodiment provides a non-fired board made of dihydrate phosphogypsum and its preparation method. Raw material for non-fired boards made from dihydrate phosphogypsum: The composition consists of 60.4 parts by weight of phosphogypsum dihydrate No. 1, 6 parts by weight of water, 0.2 parts by weight of calcium sulfate hemihydrate whiskers, 0.2 parts by weight of anhydrous gypsum, 0.3 parts by weight of sodium chloride, 0.9 parts by weight of fly ash, 0.2 parts by weight of sodium hydroxide, and 0.7 parts by weight of polycaprolactone-silane coupling agent capsule No. 1. The preparation method includes the following steps: S1. Mix dihydrate phosphogypsum No. 1, anhydrous gypsum, and fly ash according to their mass, add them to a mixer, and mix thoroughly at 500 rpm for 12 minutes to obtain a mixed powder. S2, according to the method of Example 1; S3, according to the method of Example 1; S4, according to the method of Example 1; S5, following the method of Example 1, phosphogypsum dihydrate unfired board (7d) and phosphogypsum dihydrate unfired board (28d) were obtained respectively.

[0074] Comparative Example 1 This comparative example provides a non-fired board made of dihydrate phosphogypsum and its preparation method. Raw material for non-fired boards made from dihydrate phosphogypsum: 60.7 parts by weight of phosphogypsum dihydrate No. 1, 6 parts by weight of water, 0.2 parts by weight of calcium sulfate hemihydrate whiskers, 0.2 parts by weight of anhydrous gypsum, 0.3 parts by weight of sodium chloride, 0.4 parts by weight of talc, 0.9 parts by weight of fly ash, and 0.2 parts by weight of sodium hydroxide. The preparation method includes the following steps: S1, according to the method of Example 1; S2, mix water, sodium hydroxide, sodium chloride, and calcium sulfate hemihydrate whiskers, and stir at a low speed of 400 rpm for 4 minutes to obtain a mixed solution; S3, according to the method of Example 1; S4, according to the method of Example 1; S5, following the method of Example 1, phosphogypsum dihydrate unfired board (7d) and phosphogypsum dihydrate unfired board (28d) were obtained respectively.

[0075] Comparative Example 2 This comparative example provides a non-fired board made of dihydrate phosphogypsum and its preparation method. Raw material for non-fired boards made from dihydrate phosphogypsum: The composition consists of 60.2 parts by weight of dihydrate phosphogypsum No. 1, 6 parts by weight of water, 0.2 parts by weight of anhydrous gypsum, 0.3 parts by weight of sodium chloride, 0.4 parts by weight of talc, 0.9 parts by weight of fly ash, 0.2 parts by weight of sodium hydroxide, and 0.7 parts by weight of polycaprolactone-silane coupling agent capsule No. 1. The preparation method includes the following steps: S1, according to the method of Example 1; S2, mix water, sodium hydroxide, sodium chloride and polycaprolactone-silane coupling agent capsules, and stir at a low speed of 400 rpm for 4 minutes to obtain a mixed solution; S3, according to the method of Example 1; S4, according to the method of Example 1; S5, following the method of Example 1, phosphogypsum dihydrate unfired board (7d) and phosphogypsum dihydrate unfired board (28d) were obtained respectively.

[0076] Comparative Example 3 This comparative example provides a non-fired board made of dihydrate phosphogypsum and its preparation method. Raw material for non-fired boards made from dihydrate phosphogypsum: The composition consists of 60.3 parts by weight of phosphogypsum dihydrate No. 1, 6 parts by weight of water, 0.2 parts by weight of calcium sulfate hemihydrate whiskers, 0.2 parts by weight of anhydrous gypsum, 0.4 parts by weight of talc, 0.9 parts by weight of fly ash, 0.2 parts by weight of sodium hydroxide, and 0.7 parts by weight of polycaprolactone-silane coupling agent capsule No. 1. The preparation method includes the following steps: S1, according to the method of Example 1; S2, mix water, sodium hydroxide, calcium sulfate hemihydrate whiskers and polycaprolactone-silane coupling agent capsules, and stir at a low speed of 400 rpm for 4 minutes to obtain a mixed solution; S3, according to the method of Example 1; S4, according to the method of Example 1; S5, following the method of Example 1, phosphogypsum dihydrate unfired board (7d) and phosphogypsum dihydrate unfired board (28d) were obtained respectively.

[0077] Comparative Example 4 This comparative example provides a non-fired board made of dihydrate phosphogypsum and its preparation method. Raw material for non-fired boards made from dihydrate phosphogypsum: The composition consists of 61.1 parts by weight of phosphogypsum dihydrate No. 1, 6 parts by weight of water, 0.2 parts by weight of calcium sulfate hemihydrate whiskers, 0.2 parts by weight of anhydrous gypsum, 0.3 parts by weight of sodium chloride, 0.4 parts by weight of talc, 0.2 parts by weight of sodium hydroxide, and 0.7 parts by weight of polycaprolactone-silane coupling agent capsule No. 1. The preparation method includes the following steps: S1, mix dihydrate phosphogypsum No. 1, anhydrous gypsum, and talc powder according to their mass, add them to a mixer, and mix thoroughly at 500 rpm for 12 minutes to obtain a mixed powder; S2, mix water, sodium chloride, calcium sulfate hemihydrate whiskers and polycaprolactone-silane coupling agent capsules, and stir at a low speed of 400 rpm for 4 minutes to obtain a mixed solution; S3, according to the method of Example 1; S4, according to the method of Example 1; S5, following the method of Example 1, phosphogypsum dihydrate unfired board (7d) and phosphogypsum dihydrate unfired board (28d) were obtained respectively.

[0078] Comparative Example 5 This comparative example provides a non-fired board made of dihydrate phosphogypsum and its preparation method. The raw materials for the dihydrate phosphogypsum-free board are prepared according to the method in Example 1; The preparation method includes the following steps: S1, according to the method of Example 1; S2, according to the method of Example 1; S3, according to the method of Example 1; S4. Place the compaction mold containing the mixed wet material into the pressure equipment. Starting from an initial state of 25℃ and 1 atm, pressurize to 10MPa at a rate of 0.2MPa / s and maintain the pressure. Heat to 50℃ at a rate of 10℃ / min and maintain the pressure and temperature for 10min. Stop heating and simultaneously unload the pressure at a rate of 0.2MPa / s. After depressurization, allow the material to cool naturally to 25℃ before removing it. S5, following the method of Example 1, phosphogypsum dihydrate unfired board (7d) and phosphogypsum dihydrate unfired board (28d) were obtained respectively.

[0079] Comparative Example 6 This comparative example provides a non-fired board made of dihydrate phosphogypsum and its preparation method. The raw material for non-fired boards made of dihydrate phosphogypsum is the same as in Example 1, except that dihydrate phosphogypsum No. 1 is replaced with dihydrate phosphogypsum No. 2. The preparation method was the same as in Example 1, and phosphogypsum dihydrate unfired boards (7d) and phosphogypsum dihydrate unfired boards (28d) were obtained respectively.

[0080] Comparative Example 7 This comparative example provides a non-fired board made of dihydrate phosphogypsum and its preparation method. The raw material for non-fired boards made of dihydrate phosphogypsum is as described in Example 1; The preparation method includes the following steps: When all the raw materials are added together, the mixture quickly loses its fluidity and clumps together, rendering it unusable and therefore not suitable for further testing.

[0081] Test case According to JC / T799-2016 "Decorative Gypsum Board", the breaking load and water absorption rate of dihydrate phosphogypsum unfired board (7d) and dihydrate phosphogypsum unfired board (28d) were tested respectively. The sample was subjected to water absorption in a spray curing chamber at 25℃ and 95% humidity until it was saturated and its mass was constant. m1 is defined as the mass of the 28-day unfired phosphogypsum dihydrate board after water absorption; m0 is defined as the mass of the 28-day unfired phosphogypsum dihydrate board before water absorption. Calculate the water absorption rate over 28 days; Define σ0 as the average breaking load of the 28-day unfired phosphogypsum dihydrate board before water absorption, and define σ1 as the average breaking load of the 28-day unfired phosphogypsum dihydrate board after water absorption. Calculate the softening coefficient over 28 days; Specific test data are shown in Table 1; Table 1

[0082] Examples 1 and 2 reveal that while a high proportion of all components increases the 7-day fracture load and decreases the water absorption rate, it also leads to a decrease in the 28-day fracture load and a reduction in the softening coefficient. This is because, on the one hand, the addition of organic phase change material—silane coupling agent capsules—allows for the directional arrangement of hydrophobic groups, further reducing water penetration and strengthening interfacial bonding, resulting in even lower water absorption. On the other hand, while excessive fly ash and sodium hydroxide are beneficial to strength in the early stages, the excessive CSH gel generated during the later reaction process causes volume expansion and internal microcracks, ultimately resulting in a decrease in the 28-day fracture load and softening coefficient compared to Example 1.

[0083] As observed in Examples 1 and 8, the absence of anhydrous gypsum leads to a certain degree of decrease in the softening coefficient, and the 7-day and 28-day fracture load fluctuations are relatively small. The reason is that anhydrous gypsum, as a crystal form regulator, can precisely control the thermodynamic dissolution balance of dihydrate gypsum, promote the directional growth of crystals on the (010) and (110) crystal planes, and optimize the crystal morphology and packing density. After the absence of anhydrous gypsum, the crystal growth direction is disordered, the surface roughness increases, and water is more likely to adhere and penetrate, resulting in a decrease in the softening coefficient, but the overall product is still usable.

[0084] Examples 1 and 9 show that the absence of talc leads to a decrease in the 7-day and 28-day fracture load, an increase in water absorption, and a decrease in the softening coefficient. The reason is that talc, as a plasticity modifier, can quickly penetrate and fill the large pores in the matrix during the compaction stage, improving the material's molding fluidity, making the internal structure more uniform, and avoiding local stress concentration. Without talc, the large pores cannot be effectively filled, and the uniformity of the internal structure decreases. This not only reduces the flexural strength but also increases the water penetration channels, leading to an increase in water absorption and a decrease in the softening coefficient. However, the material is still usable overall.

[0085] As observed in Example 1 and Comparative Example 1, the absence of the organic phase change material-silane coupling agent capsule leads to a decrease in 28-day fracture load, a significant increase in water absorption, and a significant decrease in softening coefficient. This is because the silane coupling agent released after the capsule ruptures can enhance the interfacial compatibility between the inorganic powder and the matrix, reduce interfacial defects, and simultaneously form a protective layer through the directional arrangement of hydrophobic groups, shortening the water penetration path. Furthermore, its synergistic dynamic thermo-pressing process can accelerate the dissolution and recrystallization of gypsum crystals, improving the degree of densification. Direct use of the silane coupling agent weakens the interfacial bonding force, renders the hydrophobic protection ineffective, and allows water molecules to easily penetrate the matrix, accelerating the dissolution of gypsum crystals. This results in a decrease in interfacial bonding force, a loose structure, and ultimately, a comprehensive reduction in strength and water resistance.

[0086] As observed in Example 1 and Comparative Example 2, the absence of gypsum whiskers leads to a decrease in fracture load at both 7 days and 28 days, with slight fluctuations in water absorption and softening coefficient. This is because the fibrous structure of gypsum whiskers can bridge microcracks within the matrix, hindering crack propagation and guiding gypsum crystals to grow oriented along the (010) and (110) crystal planes, thus improving structural regularity and density. After the whiskers are missing, the matrix loses its "skeleton support" function, microcracks tend to spread rapidly, and the looseness of crystal stacking increases, resulting in a decrease in fracture load.

[0087] As observed in Example 1 and Comparative Example 3, the absence of sodium chloride significantly reduced the fracture load at both 7 days and 28 days, while the water absorption rate and softening coefficient fluctuated slightly. This is because sodium chloride, as an ion regulator, can significantly increase the solubility of phosphogypsum under pressure and the number of defects on the particle surface, accelerating the dissolution creep of gypsum crystals and the recrystallization of solute, thereby increasing the densification and packing rate. After the absence of sodium chloride, the ion gradient of the solution becomes unbalanced, the dissolution-recrystallization efficiency of gypsum crystals decreases, the porosity inside the matrix increases, and the number of structural defects increases, directly leading to a decrease in flexural strength, which manifests as a reduction in fracture load.

[0088] As observed in Example 1 and Comparative Example 4, the alkali-activated system composed of fly ash and sodium hydroxide cannot be formed without fly ash, resulting in a significant degradation of various properties. The reason is that the alkali-activated system achieves long-term densification through three-stage dynamic regulation: the compaction stage fills large pores, the early curing stage generates CSH gel to fill micropores, and the later curing stage forms a delayed-reaction reinforcing phase to repair micro-damage. Without this system, there is no gel to fill the pores, resulting in extremely poor densification. The matrix is ​​loose and porous, which not only significantly reduces the fracture load but also provides a large number of permeation channels for moisture and corrosive media, leading to a comprehensive deterioration of water resistance.

[0089] As observed in Example 1 and Comparative Example 5, the absence of dynamic thermo-pressing process resulted in a significant decrease in the 7-day and 28-day fracture load, a substantial increase in water absorption, and a decrease in the softening coefficient. This is because the dynamic thermo-pressing process can couple the rupture of the capsule wall material with the slow release of the coupling agent, while simultaneously accelerating the efficiency of phosphogypsum crystal dissolution-creep-recrystallization. With single-stage heating, the dissolution-recrystallization rate of gypsum under low pressure is slowed down, and the release rate of the coupling agent in the capsule is reduced. The high open porosity inside the matrix allows for easy and large-scale water intrusion, leading to a significant decrease in fracture load and water resistance.

[0090] As observed in Example 1 and Comparative Example 6, replacing phosphogypsum dihydrate No. 1 with phosphogypsum dihydrate No. 2 significantly reduced the fracture load of the samples and worsened their water resistance. This is because, on the one hand, calcium sulfate dihydrate in phosphogypsum is the matrix for the densification reaction, and its content directly affects the product performance; on the other hand, silica has extremely low reactivity and high hardness, and its increased content affects the continuity of the densified interface, thereby inducing more cracks and ultimately leading to a general decrease in various properties.

[0091] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A method for preparing a non-fired board made of phosphogypsum dihydrate, characterized in that, The preparation method includes the following steps: S1, mix dihydrate phosphogypsum, optional crystal form regulator, optional plasticity regulator, and mineral admixture to obtain a mixed powder; The dihydrate phosphogypsum was subjected to desilication flotation treatment; S2, the solvent, activator, ion regulator, gypsum whiskers and organic phase change material-silane coupling agent capsules are mixed to obtain a mixed solution; S3, mix the mixed powder and mixed solution, press them to obtain dihydrate phosphogypsum non-fired board; The pressing process includes at least two stepped heating stages, where the temperature of the (n+1)th heating stage is higher than the temperature of the nth heating stage, and n is a positive integer greater than or equal to 1.

2. The preparation method according to claim 1, characterized in that, The raw materials for the dihydrate phosphogypsum non-fired board include: 40-80 parts by weight of dihydrate phosphogypsum, 5-10 parts by weight of solvent, 0.1-0.5 parts by weight of gypsum whiskers, 0.1-0.5 parts by weight of crystal form regulator, 0.1-0.5 parts by weight of ion regulator, 0.1-0.5 parts by weight of plasticity regulator, 0.5-1.5 parts by weight of mineral admixture, 0.1-0.5 parts by weight of activator, and 0.1-1.0 parts by weight of organic phase change material-silane coupling agent capsules.

3. The preparation method according to claim 2, characterized in that, The raw materials for the dihydrate phosphogypsum non-fired board include: 50-70 parts by weight of dihydrate phosphogypsum, 6-8 parts by weight of solvent, 0.1-0.3 parts by weight of gypsum whiskers, 0.1-0.3 parts by weight of crystal form regulator, 0.2-0.5 parts by weight of ion regulator, 0.3-0.5 parts by weight of plasticity regulator, 0.6-1.2 parts by weight of mineral admixture, 0.1-0.3 parts by weight of activator, and 0.5-1.0 parts by weight of organic phase change material-silane coupling agent capsules.

4. The preparation method according to claim 1, characterized in that, The pressing process includes two stepped heating stages; Optionally, the pressing conditions include: starting from an initial state of 20-25℃ and standard atmospheric pressure, increasing the pressure to 5-20MPa at a rate of 0.1-0.5MPa / s and maintaining the pressure constant; heating to 35-50℃ at a rate of 5-15℃ / min and maintaining the pressure and temperature for 1-10min; maintaining a constant pressure and continuing to increase the temperature to 60-80℃ at a rate of 5-15℃ / min and maintaining the pressure and temperature for 1-10min; stopping heating and simultaneously unloading the pressure at a rate of 0.1-0.3MPa / s; after depressurization, allowing the material to cool naturally to 20-25℃ before removing it.

5. The preparation method according to claim 4, characterized in that, The pressing conditions include: starting from an initial state of 20-25℃ and standard atmospheric pressure, increasing the pressure to 10-15MPa at a rate of 0.1-0.3MPa / s and maintaining the pressure constant, heating to 35-40℃ at a rate of 8-12℃ / min and maintaining the pressure and temperature for 1-5min; keeping the pressure constant, continuing to increase the temperature to 60-65℃ at a rate of 8-12℃ / min and maintaining the pressure and temperature for 1-5min.

6. The preparation method according to claim 1, characterized in that, The organic phase change material-silane coupling agent capsule uses the organic phase change material as the shell material and the silane coupling agent as the core material. Optionally, the organic phase change material-silane coupling agent capsule has a particle size of 5-20 μm, a shell thickness of 1-3 μm, a phase change enthalpy of 80-100 J / g, and a shell breaking temperature of 60-65℃. Optionally, the mass ratio of the silane coupling agent to the organic phase change material is (3-4):(6-7); Optionally, the organic phase change material includes polycaprolactone and / or phase change paraffin; Optionally, the silane coupling agent includes at least one of KH-550 silane coupling agent, KH-540 silane coupling agent, and KH-792 silane coupling agent.

7. The preparation method according to any one of claims 1-6, characterized in that, The preparation method of the organic phase change material-silane coupling agent capsule includes the following steps: (1) Mix the organic phase change material, silane coupling agent, and good solvent to obtain the oil phase; (2) Mix water and emulsifier to obtain an aqueous phase; (3) Add the oil phase to the water phase and mix to obtain an O / W type emulsion. Heat, separate, wash and dry to obtain organic phase change material-silane coupling agent capsules.

8. The preparation method according to claim 1, characterized in that, The CaSO4 of the dihydrate phosphogypsum The 2H2O content is ≥85wt%, the SiO2 content is ≤5wt%, the median particle size is 50-150μm, the residue on a 0.15mm square hole sieve is ≤5wt%, and it is in the form of flakes; Optionally, the desilication flotation includes the following steps: mixing the material after sieving dihydrate phosphogypsum through a 0.15mm square hole sieve with water, dispersant, inhibitor, cationic collector, and frother, performing a coarse-scavenging reverse flotation, filtering, and drying; Optionally, the mass ratio of material to water is 1:(2-4); Optionally, the mass ratio of the material to the dispersant is 10000:(1-5); Optionally, the dispersant includes at least one of water glass, sodium hexametaphosphate, and sodium fluoride; Optionally, the mass ratio of the material to the inhibitor is 10000:(1-5); Optionally, the inhibitor includes at least one of starch and carboxymethyl cellulose; Optionally, the mass ratio of the material to the cationic collector is 10000:(1-5); Optionally, the cationic collector includes at least one of tetradecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, and octadecyltrimethylammonium chloride; Optionally, the mass ratio of the material to the foaming agent is 10000:(1-5); Optionally, the foaming agent includes at least one of methyl isobutyl methanol and pine oil; Optionally, the conditions for reverse flotation include: a temperature of 20-25℃, a rotation speed of 1500-2000 r / min, a roughing flotation time of 3-8 min, and a scavenging flotation time of 3-8 min. And / or, the crystal form regulator includes anhydrous gypsum and / or citric acid; Optionally, the anhydrous gypsum is type II anhydrous gypsum with a CaSO4 content ≥90wt% and a median particle size of 40-100μm; And / or, the plasticity modifier includes at least one of talc, mica powder, and montmorillonite; Optionally, the talc powder has a SiO2 content ≥60wt%, an MgO content ≥30wt%, and a median particle size of 3-10μm; And / or, the mineral admixture includes blast furnace slag powder and / or fly ash; Optionally, the blast furnace slag powder conforms to GB / T 18046-2017 standard and has a specific surface area of ​​350-450 m². 2 / kg, 7d activity index ≥75%, 28d activity index ≥95%; Optionally, the fly ash is Class I fly ash, conforming to GB / T 1596-2017 standard, with a loss on ignition ≤5wt% and a specific surface area ≥300m² / kg; And / or, the activator includes sodium hydroxide and / or potassium hydroxide; Optionally, the sodium hydroxide is industrial-grade flaky caustic soda with a purity ≥96wt%, a moisture content ≤1wt%, and an insoluble matter content ≤0.05wt%. And / or, the ion regulator includes at least one of sodium chloride, sodium sulfate, potassium chloride, and aluminum sulfate; And / or, the gypsum whiskers include α-type calcium sulfate hemihydrate whiskers and / or β-type calcium sulfate hemihydrate whiskers; Optionally, the gypsum whiskers have a length of 50-200 μm, a diameter of 1-5 μm, and an aspect ratio of (20-50):

1.

9. The preparation method according to claim 1, characterized in that, In step S1, the mixing speed is 400-600 rpm and the time is 10-15 min; And / or, in step S2, the mixing speed is 300-500 rpm and the time is 3-5 min; And / or, in step S3, the mixing speed is 120-180 rpm and the mixing time is 5-10 min.

10. A non-fired board made of phosphogypsum dihydrate prepared by any one of claims 1-9.